Long‐Term Outcomes of Peripheral Artery Disease in Veterans: Analysis of the Peripheral Artery Disease Long‐Term Survival Study (PEARLS) - Saket Girotra; Qiang Li; Mary Vaughan‐Sarrazin; Brian C. Lund; Mohammad Al‐Garadi; Joshua A. Beckman; Rohit Nathani; Richard M. Hoffman; Paul S. Chan; Subhash Banerjee; Shirling Tsai; Dharam J. Kumbhani; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Contemporary research in peripheral artery disease (PAD) remains limited due to lack of a national registry and low accuracy of diagnosis codes to identify patients with PAD. Methods Leveraging a novel natural language processing system that identifies PAD with high accuracy using ankle‐brachial index and toe‐brachial index values, we created a registry of 103 748 patients with new‐onset PAD in the Veterans Health Administration. Study end points include mortality, cardiovascular events (hospitalization for acute myocardial infarction or stroke) and limb events (hospitalization for critical limb ischemia or major amputation) and were identified using Veterans Affairs and non–Veterans Affairs encounters. Results The mean age was 70.6 years; 97.3% were male, and 18.5% self‐identified as Black. The mean ankle‐brachial index value was 0.78 (SD: 0.26) and the mean toe‐brachial index value was 0.51 (SD: 0.19). A majority of patients were current (27.1%) or former (30.0%) smokers. Prevalence of hypertension (86.6%), heart failure (22.7%), diabetes (54.8%), chronic kidney disease (23.6%), and chronic obstructive pulmonary disease (35.4%) was high. At 1 year, 9.4% of patients had died. The 1‐year incidence of cardiovascular events was 5.6 per 100 patient‐years and limb events was 7.0 per 100 patient‐years. Conclusions We have successfully launched a registry of >100 000 patients with a new diagnosis of PAD in the Veterans Health Administration, the largest integrated health system in the United States. The incidence of death and clinical events in our cohort is high. Ongoing studies will yield important insights regarding improving care and outcomes in this high‐risk group.